(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
The scientific activity occurs under influences of scientific, academic and social politics. In Brazil, particularly, the work to produce scientific knowledge depends intensely on these conditions. The possibilities to produce knowledge in experimental analysis of the behavior and its results, either scientific or technological and social, are still limited by unfamiliarity or prejudice. The organization of the behavior analysts, their participation in the system of the country’s science development, technology and higher education is an important condition for the development of this area in psychology. An only circumstantial organization, improvised or located in geographic areas or non representative groups will run the risk of becoming inefficient and have little force or durability. Organization and representation depend on conditions for representation. All this require a basic structure of relationship and work towards supporting the organization, the participation and the representation. All these conditions, in turn, strongly depend on a gradual qualification and perfectioning of the behavior analysts so that the development of the AEC in the country is evaluated not only by amount of publications, events or participation in them. The volume of production and activity needs to also express an upgrade in the quality of the production, the formation of new analysts, the permanent perfectioning, a deep update of the currently operating ones, in the improvement of the conditions of knowledge production on the behavior and the spreading and diffusion of this knowledge and in the formation of new generations of psychologists. In the first decade of the XXI Century, publications already exist, programs of post-graduation and courses directed toward this knowledge and the performance of the behavior analysts. It seems to be a good moment to evaluate what, historically, has been made with the associations and attempts to their organization in national, regional or local levels and to start a work to allow for more organization, participation and representation of the AEC in the system of development of science, technology and higher education in the country, regardless of how precarious it might still be or how incipient the initial efforts to construct these conditions.